Cervical myelopathy caused by IgG4-related hypertrophic spinal pachymeningitis: Case report and a descriptive review of the literature - Ahmet Parlak; Christian-Andreas Mueller; Kay W. Nolte; Tobias P. Schmidt; Ulf Bertram; Hans Clusmann; Christian Blume (Brain and Spine)
Introduction: IgG4-related disease is an immune-mediated condition characterized by tissue infiltration of IgG4-positive plasma cells. Involvement of the spinal meninges results in hypertrophic spinal pachymeningitis (HSP), causing spinal cord and nerve root compression. Research question and case description: In this review, we present a case of IgG4-related hypertrophic spinal pachymeningitis. Furthermore, we provide an updated literature review on IgG4-related HSP. Materials and methods: We describe the case of a 45-year-old male presenting with cervical myelopathy. MR-imaging showed a ventrodorsal thickening of the meninges resulting in spinal cord compression. The patient underwent surgical decompression through laminectomy and excision of the dural thickening. The pathological findings demonstrated hypertrophic pachymeningitis with further examination showing large-scale dural infiltration of IgG4-positive lymphocytes. Adjuvant therapy with methylprednisolone and rituximab resulted in full neurological recovery with no signs of recurrence on MRI or clinically 12 months postoperatively.An updated review of the literature regarding IgG4-related HSP was performed according to PRISMA-guidelines. Relevant articles were searched from the PubMed, Web of Science and Embase databases. Patient characteristics, MRI- and histopathological findings, treatment modality and outcome were reviewed. Results: The literature review provided a summary of 52 available cases, which included the one cases from our centre. Progressive worsening of neurological impairment was observed in 28 patients (58%). The lesions involved the thoracic spine (n = 33, 62.2%), cervical spine (n = 35, 70%), lumbar spine (n = 10, 20%), and sacral spine (n = 1, 2.2%). The dural thickening typically appeared as striated, fusiform, or oval changes, with homogeneous and patterns being the most common. Surgical decompression followed by immunosuppressive treatment was the main choice of therapy. The disease proved fatal in one case. Discussion and conclusion: IgG4-related HSP usually affects the cervical and thoracic dura and therefore often presents with myelopathy. Surgical decompression in cases of neurological deficits may prevent permanent neurological impairment. Immunosuppressive therapy constitutes the cornerstone in the treatment IgG4-related HSP.